2015
DOI: 10.1007/s00170-015-7336-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic characterization of machining robot and stability analysis

Abstract: Machining robots have major advantages over cartesian machine tools because of their flexibility, their ability to reach inaccessible areas on a complex part, and their important workspace. However, their lack of rigidity and precision is still a limit for precision tasks. Innovations and design optimization of robotic structure, links, and power transmission allow robot manufacturers to propose business solutions for machining applications. Beyond accuracy problems, it is also necessary to quantify the vibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(44 citation statements)
references
References 13 publications
0
37
0
1
Order By: Relevance
“…Their results showed that cutting force was reduced by 50-70% compared with using a fluting machine. In a high-speed machining category, Mejri et al [115] observed dynamic characterisation of robotic machining system. Cutting conditions should be adaptively changed along with robot posture to ensure stability in terms of dynamic property differences, as shown in Fig.…”
Section: Machining Processmentioning
confidence: 99%
“…Their results showed that cutting force was reduced by 50-70% compared with using a fluting machine. In a high-speed machining category, Mejri et al [115] observed dynamic characterisation of robotic machining system. Cutting conditions should be adaptively changed along with robot posture to ensure stability in terms of dynamic property differences, as shown in Fig.…”
Section: Machining Processmentioning
confidence: 99%
“…The modulus plot highlights the presence of the fundamental mode at about 13 Hz, and the phase plot corroborates this fact, showing large phase changes at the same frequency. The tests were carried out with the modal analysis approach [20], which is widely used in the fields of automotive engineering [21,22], aerospace engineering [23], automatic machines [24], and robotics [25]. A grid of measurement points was defined on the robot (see Figure 5); points 10 and 11 were used to monitor base vibrations.…”
Section: Testing Equipment and Methodsmentioning
confidence: 99%
“…The experimental identification carried out by Mejri et al [5] enables the determination of the actual modal parameters of the robot structure in a given position and configuration where the tests are performed. It is not valid for other positions and configurations of the robot, but they are usually required as an effective means to calibrate numerical models.…”
Section: Identification Of Robot Parametersmentioning
confidence: 99%
“…Mejri et al [5] experimentally investigated the end-effector position effect on the dynamic behavior of an ABB IRB6660 robot. They observed modifications in the robot's dynamic behavior depending on changes in its posture.…”
Section: Introductionmentioning
confidence: 99%